Fast temperature measurement following single laser-induced cavitation inside a microfluidic gap - Quinto-Su, Pedro A. (2014)
Single transient laser-induced microbubbles have been used in microfluidic chips for fast actuation of the liquid (pumping and mixing), to interact with biological materials (selective cell destruction, membrane permeabilization and rheology) and more recenty for medical diagnosis. However, the expected heating following the collapse of a microbubble (maximum radius ~ 10–35 µm) has not been measured due to insufficient temporal resolution. Here, we extend the limits of non-invasive fluorescence thermometry using high speed video recording at up to 90,000 frames per second to measure the evolution of the spatial temperature profile imaged with a fluorescence microscope. We found that the temperature rises are moderate (< 12.8°C), localized (< 15 µm) and short lived (< 1.3 ms). However, there are significant differences between experiments done in a microfluidic gap and a container unbounded at the top, which are explained by jetting and bubble migration. The results allow to safe-guard some of the current applications involving laser pulses and photothermal bubbles interacting with biological material in different liquid environments.